Multifocal choroiditis and panuveitis (MCP) – diagnosis, ocular symptoms and treatment - Brydak-Godowska, Joanna; Śwituła, Marcin; Dróbecka-Brydak, Ewa; Mzyk, Marzena; Sędrowicz, Elżbieta; Samsel, Agnieszka (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Multifocal choroiditis and panuveitis (MCP) belong to white dot syndromes, which are an idiopathic inflammatory process damaging the retinal pigment epithelium and choriocapillaris. We observed fourteen patients with typical ocular changes for MCP (panuveitis with typical multiple yellow, white or gray focal lesions in fundus of the eye). In 8 patients typically were observed – glaucoma, cataract, macular edema. We applied topical drops (corticosteroids, antiglaucomatous), and in 5 patients oral encorton was necessary to include.